BIOGEOGRAPHY AND ECOLOGY OF THE MANGROVES ECOSYSTEM FROM THE SEMIARID SEPTENTRIONAL COAST OF BRAZIL - Silva, Edson Vicente da; Cestaro, Luiz Antonio; Rabelo, Francisco Davy Braz (Ra'e Ga: o Espaço Geográfico em Análise, 2020)
The northern coast of Brazil presents a section where the semi-arid climate determines particular characteristics to the estuaries and mangroves. The objective of this work was to segment the mangroves of this section and describe the distribution of the species of flora and fauna in the ecosystem, according to the different environmental compartments, and enumerating the main environmental services carried out by the mangroves in the region. The study area extends from the estuary of the Cardoso and Camurupim rivers in Luís Correia in Piauí (41 ° 28 'long S) to the Cabo de Calcanhar in Touros in Rio Grande do Norte (35 ° 29' 22 "S), in an approximately 760 km extension. The driest climate, BSh, controls from Areia Branca (RN) to Pedra Grande (RN). Most of the area is under a slightly wetter climate, Aw, with a longer annual wet period, extending for four to five months. Five sectors were identified and delimited where mangroves are more similar to each other. Four associations of plant species were identified, whose distribution is associated with the mangrove internally dominant environmental characteristics. The dominant fauna species are presented for sites according to the frequency of flooding by the tides. At the end, the functions and environmental services identified for local mangroves are listed. The semi-arid climate exerts a strong influence on local mangroves, both in the development of plant species and in the internal distribution of plant associations.